Reconsidering reproductive patterns in a model dissociated species, the red-sided garter snake: Sex-specific and seasonal changes in gonadal steroidogenic gene expression - Lincoln, Julianna M.; Barlowe, Megan L.; Rucker, Holly R.; Parker, M. Rockwell (Frontiers in Endocrinology, 2023)
Sex steroid hormones are powerful regulators of reproductive behavior and physiology in vertebrates, and steroidogenesis has distinct sex- and season-specific patterns ultimately dictated by the expression of key enzymes. Most comparative endocrinology studies, however, focus only on circulating levels of sex steroids to determine their temporal association with life-history events in what are termed associated reproductive patterns. The red-sided garter snake (Thamnophis sirtalis parietalis) is a notable exception; this species exhibits maximal sex behavior decoupled from maximal sex steroid production and gametogenesis in what is termed a dissociated reproductive pattern. And while this is true for male red-sided garter snakes and their production of testosterone, females have maximal estradiol production during peak breeding (spring) but only immediately after mating. Here, we demonstrate that expression of ovarian aromatase (conversion of androgens to estrogens) matches the established seasonal hormone pattern in females. Additionally, steroidogenic gene expression in the ovary is broadly reduced if not suppressed compared to the testis throughout the active year. Bizarrely, male red-sided garter snakes demonstrate an unexplained pattern of steroidogenic gene expression in the testis. StAR (import of cholesterol to steroidogenesis) is maximally expressed in spring, yet Hsd17b3 expression (conversion of androstenedione to testosterone) is highest in summer, with the latter matching the established summer peak in male testosterone. The function of elevated StAR in spring is unknown, but our results suggest a decoupling between maximal StAR expression and testosterone biosynthesis (Hsd17b3 expression). We also purport that the reproductive pattern binary should be reassessed given its lack of fit for many vertebrate species that demonstrate seasonal, mixed patterns of (a)synchrony between circulating sex hormones and reproductive behavior.